English Education for Elderly Empowerment in the Green Economy Program - -, Siswantini; Indahyani, Titi; Soraya, Kiky (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2025)
This study examines the implementation of the English for Green Economy Program, designed to empower pre-elderly and elderly learners through English education integrated with sustainability and entrepreneurship. The program aimed to develop participants’ language competence, eco-literacy, and entrepreneurial awareness within the framework of lifelong learning. A mixed-method descriptive–evaluative design was employed, involving twenty participants aged 45–70 who were active in community-based environmental and entrepreneurial groups. Data were collected through a structured questionnaire consisting of four sections: program evaluation, trainer performance, training benefits, and participant feedback. Quantitative data were analysed descriptively, while qualitative comments were thematically interpreted. The overall results indicated strong positive perceptions, with 61% of all responses rated “Strongly Agree” and the remaining 39% “Agree.” Specifically, 95% of participants confirmed the program’s relevance, 80% highly valued the trainer’s performance, and 75% reported enhanced skills applicable to daily and entrepreneurial contexts. Qualitative feedback emphasized extending the duration and focusing on one topic per session to deepen understanding. These findings demonstrate that English language education, when contextually linked with sustainability and entrepreneurship, can effectively promote empowerment, environmental awareness, and lifelong learning among elderly communities.